Exploratory study on the banking behaviour of credit card users and their characteristics - Pang, May Yee (2008)
This report seeks to establish why credit card users engage in multiple or single banking and to see if there is any difference in the demographic and psychographic characteristics between the two groups. It also examines whether psychographics can better differentiate them than demographics.